(No?) Adventures in Recording Land: Engineering Conventions in Metal Music - Herbst, Jan-Peter; Mynett, Mark (Rock music studies, 2022)
Inspired by claims that metal music production has become standardized, this article draws on interviews with eight internationally recognized producers examining whether a uniform methodology in recording metal exists and where creative freedom remains. The findings suggest that although recordists must abide by electroacoustic laws and metal music's pursuit of ever-heavier music, which entails some best practices, decades-long careers build on creative experimentation and sustained curiosity. The individuality of bands, songs, arrangements, and recording conditions requires individual production approaches, and most successful producers experiment to develop professionally and stay at the forefront of contemporary metal music production practice.